Controllable synthesis of supported platinum catalysts: acidic support effect and soot oxidation catalysis. Issue 15 (3rd July 2017) - Gao, Yanxiu; Yang, Weinan; Wu, Xiaodong; Liu, Shuang; Weng, Duan; Ran, Rui
Abstract : Platinum nanoparticles were synthesized by a classic polyol process in ethylene glycol. Abstract : Platinum nanoparticles were synthesized by a classic polyol process in ethylene glycol. The Pt nanoparticles were loaded on H-ZSM5 and γ-Al2 O3 supports by wet impregnation. The as-obtained solid was thermally treated in a two-step procedure to remove the organic residues. Due to their larger particle size than the micropore size of H-ZSM5, the impregnated Pt particles were dispersed on the external surface of the zeolite support. With similar Pt particle size distribution and Pt loading, the Pt/H-ZSM5 and Pt/γ-Al2 O3 catalysts were evaluated for the oxidation of NO and soot. Despite its lower activity for NO oxidation to NO2, the Pt/H-ZSM5 exhibited a much higher activity for soot oxidation in the presence of NO + O2 . This abnormal NO x -assisted soot oxidation behaviour of Pt/H-ZSM5 was explained by the promoting effect of the acid sites on the zeolite.